Antibacterial and toxicity properties of biosynthesized silver nanoparticles by lawsonia inermis extract / Nur Syazana Satteri - Satteri, Nur Syazana (2020)
Biosynthesis of silver nanoparticles using plant extracts are currently being explored as an alternative approach in pharmaceutical and medical field. The aims of this study was synthesized and characterized silver nanoparticles (AgNPs) by using UV-Vis spectrophotometer, identified their antibacterial and toxicity activity. The biosynthesized of AgNPs were varies in the reaction time (1, 2, 3, 6 and 7) days, was characterized by UV-Vis spectrophotometer (200-600 nm). The determination of antibacterial and toxicity assays of Lawsonia inermis was done by Kirby–Bauer disc diffusion method (Gram-positive and Gram-negative bacterial strains) and Brine Shrimp Lethality Assay respectively. From the result, L. inermis leaf extract was reduced the silver ions and indicates the formation of silver nanoparticles by changing colour from dark brown to colloidal grey. The highest peak of biosynthesized silver nanoparticles from L. inermis extract in range from 420 nm to 471 nm. Zone inhibition for Gram-positive and Gram-negative bacterial strains at 1000 μg/ml was 12.00 mm and 12.33 mm respectively. The LC50 of biosynthesized AgNPs at 1000 μg/ml was observed 7367.233 which indicate non-toxic towards the brine shrimp. To conclude, AgNPs synthesized from L. inermis leaves extract would be very efficient to be an alternative for antibacterial.